Answer:
Option 3) -6,-5/2
Step-by-step explanation:
we know that
The formula to solve a quadratic equation of the form
[tex]ax^{2} +bx+c=0[/tex]
is equal to
[tex]x=\frac{-b(+/-)\sqrt{b^{2}-4ac}} {2a}[/tex]
in this problem we have
[tex]4x^{2} +34x+60=0[/tex]
so
[tex]a=4\\b=34\\c=60[/tex]
substitute in the formula
[tex]x=\frac{-34(+/-)\sqrt{34^{2}-4(4)(60)}} {2(4)}[/tex]
[tex]x=\frac{-34(+/-)\sqrt{196}} {8}[/tex]
[tex]x=\frac{-34(+/-)14} {8}[/tex]
[tex]x_1=\frac{-34(+)14} {8}=-\frac{20}{8}=-\frac{5}{2}[/tex]
[tex]x_2=\frac{-34(-)14} {8}=-6[/tex]